Ecotourism a case study - Trikojus, Tom; Hewett, Andrew (Video Education Australasia, 2002)
This program uses the Phillip Island Nature Park (PINP) as a case study to explore and illustrated the principles of ecotourism. The Philip Island Nature Park is an excellent example because it has tours and attractions at all three levels of accreditation, and has been involved in ecotourism for many years. Follow Andrew, the presenter of this programme, as he travels to all the attractions of the Phillip Island Nature Park, and meets a wide variety of people-from rangers to marketing executives.